Revisiting coffee replacement decisions in the aftermath of the 2012-2013 coffee rust event in Nicaragua - Mendoza Tijerino, Francisco Antonio (Universidad Nacional Agraria, 2023)
This article quantifies the partial effect of different coffee leaf rust infestation levels on the intensity of coffee replacement area. The analysis is made for the agricultural cycle 2012-13 by employing the 2012-13 Coffee Production Survey of the Ministry of Agriculture of Nicaragua. By means of econometric estimates, farmers coffee renewal decisions are described as a function of coffee leaf rust infestation. The results are further contrasted to the developments of coffee grown area since 2012. A significant and positive relationship is found between different levels of coffee infested area and farmers coffee replacement expectations. The results help to improve the understanding of i) the demand for re-investments, ii) farmer's entrepreneurial behavior and iii) re-investments constraints after low probability of occurrence agricultural shocks.